Os desafios do ensino inclusivo de matemática para alunos cegos: uma revisão bibliográfica acerca da alfabetização geométrica - CORRÊA, Alex Carneiro (2023)
This research presents a discussion about the pedagogical practice in mathematics, and its challenges and prospects for school inclusion. It is known that for centuries, special education was interpreted in a prejudiced way, as was understood as a form of education that sought to segregate students with special needs, outside the conventional school environments. very if advanced in the world, in legal terms, regarding special and inclusive education, understood as a right to human dignity. In Brazil, the legal frameworks advanced, understanding that everyone has the right to education, establishing education special and inclusive education as a compulsory teaching modality in regular schools. Even so, much still needs to be done, especially in terms of senses. common and prejudices that are still present in school environments in regarding inclusion. In this context, the general objective of this study is to understand through a bibliographic review, the challenges and perspectives of teaching mathematics, in the field of geometry, for blind students. Specific objectives: (I) Address the aspects of mathematical literacy, with a focus on geometry, and its interface with special and inclusive education; (II) Externalize the challenges and expectations of the geometric literacy for blind students. We base the research on review literature, book consultations, articles, master's dissertations, the different conceptions about the challenges of teaching in mathematics, within the scope of teaching geometry for blind students. We believe that although the challenges are still a reality, perspectives are drawn on the horizon of teaching practice, tools didactics such as tactile models become mechanisms to promote the teaching of geometry through touch, enabling the learning of blind students and their real inclusion in the training process.